L’accès des femmes à l’espace public : du local au national, de l’international au transnational. L’exercice de la responsabilité publique et les rapports de genre en Amérique latine - Bérengère Marques-Pereira (Centre de Recherches sur les Mondes Américains, 2008)
This paper describes the participative citizenship of the Latin-American women during the last four decades, from the seventies to the present day. We examine how women have acquired the capacity to have an impact on the public space, on balances of power and social relations – with a determination to change the latter as far as the feminist movements are concerned. This exercise of public responsibility can take three main aspects. First a reflection on the social and political exclusion of women as well as on the modalities of their inclusion. Secondly their participation to what may be called the elaboration of a social normativity. The third aspect is to keep one’s eye on the institutions and on the State agencies, reminding the Nation-States about their accountability.